The EU Anchor Thesis: Transition from Socialism, the Institutional Vacuum and Membership in the European Union - Nauro F. Campos (Institute of Labor Economics (IZA), 2021)
One of the strongest stylized facts of the transition is also one of the most unexpected: after 1989 Central and Eastern European and Former Soviet Union countries diverged massively. Institutions are a main reason. The EU anchor thesis posits that the prospect of membership in the European Union (EU) played a key role in filling in the institutional vacuum that followed the collapse of socialism. This chapter examines this thesis and assesses the relevant bodies of evidence, focusing on whether the prospect of EU membership accelerated institutional development and, if so, whether this was indeed associated with improved economic outcomes.
Keywords: O1; P2; 330; institutions; european integration